TBAI-catalyzed C–N bond formation through oxidative coupling of benzyl bromides with amines: a new avenue to the synthesis of amides. Issue 3 (1st February 2022) - Kumar, Dhirendra; Maury, Suresh Kumar; Kumari, Savita; Kamal, Arsala; Singh, Himanshu Kumar; Singh, Sundaram; Srivastava, Vandana
Abstract: A new green approach for the synthesis of amide through TBAI-catalyzed oxidative coupling of benzyl bromides with amine was developed in the presence of tert -butyl hydroperoxide (TBHP) as an oxidant. Various electron-donating and withdrawing groups containing benzyl bromides and various amines, were subjected to the reaction and transformed to the corresponding amide in good to excellent yields. Graphical Abstract: UF0001